The Effect of ATI TEAS on Admission Into Prelicensure Nursing Programs. (Journal of Nursing Education, 2025)
Background: Assessment Technologies Institute (ATI) Test of Essential Academic Skills (TEAS) and grade point average (GPA) are commonly used cognitive parameters to determine student admission and success in associate degree in nursing and Bachelor of Science in Nursing programs. The efficacy of such parameters should be evaluated to promote an equitable admissions process. Method: Utilizing an exploratory research design, historical enrollment trends were analyzed to evaluate the effect on new student admission. Pearson's correlation was used to understand the correlation between ATI TEAS scores and extracted GPA. Results: The new admission standards resulted in a nearly 75% decrease in new student enrollment. No correlation was found between extracted GPA and ATI TEAS domain scores or extracted GPA and overall ATI TEAS success. Conclusion: Admissions standards should assess students' cognitive and non-cognitive abilities while striking a balance between concerns about enrollment, attrition, diversity, and program outcomes. Institutions should strive to establish mission-driven admission policies, fully acknowledging the barriers, potential implications, and predictability of each measure.